Operation of a Fuzzy Controlled Half-Bridge DC-Converter as a Welding Current-Source - Zahra Malekjamshidi; Mohammad Jafari; Kourosh Mahmoodi (Universitas Ahmad Dahlan, 2012)
A new Fuzzy controlled welding machine (FCWM) current source is introduced in this paper and the results of the new control method are explained. The Fuzzy controller is applied to the welding machine to improve some problems of welding process. The new intelligent controller guaranties a constant current during welding to improve welding quality. It also provides some features such as hot-start and anti-stuck function and a standby mode for energy saving. The effectiveness of this intelligent welding machine was proven by the experimental results and durable test. The results show that designed FCWM can be used in mobile welding industries.